Calcium-induced calcium release in EGTA-skinned aortic strips from genetically hypertensive and normotensive rats - Aiello, Ernesto Alejandro (1995)
The release of 45Ca induced by Ca2+ was studied in genetically hypertensive (SHR) and normotensive (WKY) rats using EGTA-skinned aortic strips. Strips preloaded with 45Ca (pCa 6.6) were desaturated at 5mM of EGTA. A slow component of the washout in aorta from SHRs exhibited higher Ca content and a lower rate of Ca leak than that in aorta from WKY rats. This slow component was stimulated during washing with 0.03, 0.3, 1 or 10μM free Ca2+. The release of 45Ca induced by Ca2+ proceeded at similar rates in preparations of the two strains. Compared to WKY aortic strips the stimulated efflux of 45Ca was greater in SHR aortic strips due to the higher Ca content. About half of the release of 45Ca induced by 1μM free Ca2+ during the first 6 minutes of stimulation was blocked by 0.6mM of ryanodine or 50μM of ruthenium red, thus identifying the sarcoplasmic reticulum as a source of Ca release. The results suggest that this intracellular storage of Ca in aorta from genetically hypertensive rats is relevant for the generation of high levels of cytosolic Ca2+.